2016
DOI: 10.4103/2152-7806.173565
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular decompression for glossopharyngeal neuralgia using intraoperative neurophysiological monitoring: Technical case report

Abstract: Background:Glossopharyngeal neuralgia (GN) is a rare functional disorder representing around 1% of cases of trigeminal neuralgia. Lancinating throat and ear pain while swallowing are the typical manifestations, and are initially treated using anticonvulsants such as carbamazepine. Medically refractory GN is treated surgically. Microvascular decompression (MVD) is reportedly effective against GN, superseding rhizotomy and tractotomy.Methods:We encountered three patients with medically refractory GN who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Greater successes have recently been reported for lower cranial nerve monitoring, methods for recording reliable MEPs from the vocal cords were introduced by Deletis et al [ 71 ], and 1 patient with intraoperative unilateral laryngeal nerve injury exhibited immediate reduction in MEPs recorded from the ipsilateral vocalis muscle. Motoyama et al recently reported their success in recording MEPs from the stylopharyngeus and vocalis muscles in two patients undergoing microvascular decompression for glossopharyngeal neuralgia [ 175 ]. Ito et al successfully recorded MEPs from the vocalis muscles in 15 patients undergoing surgery for skull base or brainstem tumors, and intraoperative changes correlated with postoperative dysphagia [ 176 ].…”
Section: Discussionmentioning
confidence: 99%
“…Greater successes have recently been reported for lower cranial nerve monitoring, methods for recording reliable MEPs from the vocal cords were introduced by Deletis et al [ 71 ], and 1 patient with intraoperative unilateral laryngeal nerve injury exhibited immediate reduction in MEPs recorded from the ipsilateral vocalis muscle. Motoyama et al recently reported their success in recording MEPs from the stylopharyngeus and vocalis muscles in two patients undergoing microvascular decompression for glossopharyngeal neuralgia [ 175 ]. Ito et al successfully recorded MEPs from the vocalis muscles in 15 patients undergoing surgery for skull base or brainstem tumors, and intraoperative changes correlated with postoperative dysphagia [ 176 ].…”
Section: Discussionmentioning
confidence: 99%